ANTIFEEDANT ACTIVITY FROM NEEM LEAF EXTRACT (Azadirachta indica A Juss) - Ridha kurniati; Nurdin Saidi; Rosnani Nasution (Jurnal Natural, 2018)
Antifeedant activity of neem leaf (A. indica A. Juss) has been identified by against Tenebrio molitor bio-indicator. The highest activity was obtained on ethyl acetate extract at 0.5% concentration having Antifeedant Index (AI) of 51.53% and most active at 10% concentration of 82.05%. The method used to test the antifeedant activity is the no choice leaf disk method. Secondary metabolites contained in neem leaf extract (A. indica A. juss) include terpenoids, steroids, flavonoids, saponins and phenolics. Keywords: Neem leaf (Azadirachta Indica A.Juss),  No choice leaf disk method, Antifeedant ActivityREFFERENCES Benge, M.D. 1986. Neem the Cornucopia Tree. S and T/FENR Agroforestation Technical Series No. 5. Agency for International Development Washington, D.C.190p.Schumutterer., H. 2002. Properties and Potensial of Natural pPsticides from Neem Tree, Azadirachta indica Ann. Rev. Entomol. 35; 271-291Alzohairy, M.A. 2016. Review Article Therapeutics Role of Azadirachta indica (Neem) and Their Active Constituents in Diseases Prevention and Treatment, Article ID 7382506, 11p.4.       Patel, S.M., Venkata., K.C.N., Bhattacharyya, P., Sethi, G., Bishayee, A. 2016. Potential of Neem (Azadirachta indica) For Prevention and treatment of Oncologic Diseases Seminar In Cancer BiologyDiabate, D., Gnago, J.A., Tano, Y., 2014. Toxicity, Antifeedant and Repellent, effect of Azadirachta indica A. Juss and Jatropa carcus L. aqueous extracts agaianst Plutella xylostella  (Lepidoptera: Plutellidae) J. Basic. Appl. Sci. Res. 4 (11) : 51 – 60Jeyasankar, A., and Gokilamani, D., 2016. Biology and eco-friendly control of Amaranth pests, Hymenia recurvalis Fabricus and Psara basalis (Lepidoptera : Crambidae) Inter. J. Acad. Stud. 2 (4): 218 – 230.Pavunraj, M., Muthu, C., Ignacimuthu,S., Janarthanan, S., Duraipandiyan, V., Raja, N. and Vimalraj, S. 2011. Antifeedant Activity of a Novel 6-(4,7-hydroxyl-heptyl)Quinone From The Leaves of The Milkweed Pergularia daemia on The Cotton Bollworm Helicoverpa armegera (Hub.) and The Tobacco Armworm Spodoptera litura (Fab.) Phytoparasitica 39 : 145 – 150.Munoz, E., Lamilla, C., Marin, J.C., Alarcon, J., Cespedes, C.L.m 2012. Antifeedant, Insect Growth and Insecticidal Effec of Calceolaria talcana (Calceolariaceae) on Dropsopphila melanogaster and Spodoptera frugiperda Industrial Crops and Product, 42, 137 – 144.Saxena, M., Saxena, J., Nema, R., Singh, D and Gupta, A. 2013. Phytochemistry of Medicinal Plants Journal pharmacognosy and Phytochemistry, 1;6.Liu, L., Zhao, Y.L., Cheng, G.G., Chen, Y.Y., Qin, angX.J., C.C.W., Yang, X.W., Liu, Y.P., Luo, X.D, 2014. Antifeedant activity and effect of fruits and seed extract of Cabralea canjerana canjerana (Vell.) Mart. (Meliaceae) on the immature stages of the fall armworm Spodoptera frugiperda (JE Smith) (Lepidoptera: Noctuidae Crops and Product. 65 ; 156 – 158.Schoonhven, LM. 1982. Biologycal Aspect of Antifeedant . Ent, Exp and Appl  .31: 57 - 69Gahukar, R.T. 2014. Factor Affecting Content and Bioefficacy of Neem (Azadirachta indica A. Juss) Phytochemicals used in Agriculture pest control A Review. Crop Protection. 62: 93 – 99.Pattanaik, S.J., Ranghupati, N.D.,Chary, P.2006.Ecomorphometric Marker Reflect Variation in Azadirachtin Contents of Azadirachta indica A. Juss. (Meliaceae) in Select Regions of Andhra Pradesh India. Curr. Sci, 91:628 – 636.Adel, M.M., Sehnal, H., Jurzysta, M. 2000. Effects of Alfalfa safonin on the Moth Spodoptera litura Journal of Chemical Ecology, 26 : 7-14Shuklar, Y.N., Rani, A. Tripathi,A.K., Sharma, S. 1996. Antifeedant, Activity of Ursolic Acid Isolation from Duboisia myoporoides Phytotheraphy, 10 : 359 – 360Walter, J.F. 1999. Commercial With Neem Product, P. 155-170. In Franklin R, Hall and Julius J. Menn. Biopesticides Use and Delivery. Humana Press. Totowo, New Jersey.